INTERAKSI SOSIAL DI ERA DIGITAL: PERUBAHAN BENTUK DAN FAKTOR TEKNOLOGI SEBAGAI PENDORONG UTAMA - Wawan; Fahresi; Samsinar Syarifuddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Social interaction is a dynamic relationship that occurs between individuals, between individuals and groups, and among different groups. This process plays a crucial role in social life as it enables communication, cooperation, exchange of ideas, and problem-solving. Social interaction is generally categorized into two types: associative interaction, which promotes unity such as cooperation, accommodation, and assimilation, and dissociative interaction, which leads to division such as competition, contravention, and conflict. In school and community environments, social interaction plays an important role in shaping character traits such as discipline, responsibility, social awareness, and the ability to live harmoniously with others. By understanding social interaction, individuals are expected to appreciate differences, improve social relationships, and prevent harmful conflicts.